Immunogenetics and infectious diseases: special reference to the mayor histocompatibility complex - Alves,Crésio (2006)
Many studies have tried to identify genetic markers for infectious diseases, some of them have focused on human leukocyte antigens (HLA). The products of HLA genes interact with surface-specific receptors of T lymphocytes, resulting in activation of the host's immune response. Association of bacterial, viral, parasitic and fungal infections with the host's HLA has been widely investigated. The type and strength of this association differs among distinct populations, as well as among racial and/or ethnic groups. The new molecular methods for the identification of the HLA alleles, and the resulting new nomenclature, have contributed to a better understanding of this system. Unfortunately, this information has not been adequately transmitted to clinicians, which hampers the understanding of the association between the HLA system and diseases. We revised relevant studies on the association of HLA genes with infectious diseases, demonstrating their importance in the pathogenic mechanisms, through increased susceptibility or protection against infections and their complications.